Bamboo-inspired ultra-strong nanofiber-reinforced composite hydrogels - Hao Zhuo; Xinyu Dong; Quyang Liu; Lingyi Hong; Zhaolong Zhang; Shuchang Long; Wei Zhai (Nature Communications)
Abstract Biological materials, such as bamboo, are naturally optimized composites with exceptional mechanical properties. Inspired by such natural composites, traditional methods involve extracting nanofibers from natural sources and applying them in composite materials, which, however, often results in less ideal mechanical properties. To address this, this study develops a bottom-up nanofiber assembly strategy to create strong fiber-reinforced composite hydrogels inspired by the hierarchical assembly of bamboo. Self-assembled chitosan-sodium alginate nanofibers (CSNFs) are combined with tannic acid (TA) and poly(vinyl alcohol) (PVA) as the interfacial crosslinker and hydrogel matrix, respectively, to emulate the fundamental cellulose-lignin-hemicellulose composition unit of bamboo. Strong interfacial electrostatic interactions and hydrogen bonding form between the functional groups of these components. These molecular interactions can be further reinforced by constructing higher-order structure through stretch-induced orientation. The resulting composite hydrogel achieves good mechanical performance, including a high tensile strength of up to 60.2 MPa and a simultaneous high strength of 48.0 MPa and ultimate strain of 470%. This approach demonstrates a hierarchical bottom-up strategy to construct strong and robust composite hydrogels by effectively leveraging fundamental molecular interactions. By mimicking bamboo’s highly integrated structural composition, it offers a promising solution for creating advanced bioinspired materials with excellent mechanical properties.